Wound infection and pain one month after trauma: an underestimated threat - Kateryna Ksenchyna; Oleh Ksenchyn; Dmytro Dmytriiev; Oleksandr Nazarchuk (Frontiers in Pain Research)
BackgroundPain is a common complication after combat injuries to the extremities. The role of nerve damage in the development of post-traumatic pain is recognized and described in the literature, superinfection as a potential factor has not been studied sufficiently.ObjectiveTo establish the relationship between the characteristics of the wound microbiota, the intake of different groups of antibiotics and the development of chronic pain in patients with traumatic injuries of the extremities.MethodsWe conducted a prospective study that included 56 patients. All participants were male, aged 25 years and older. In addition, a mandatory inclusion criterion in the study was the presence of prolonged wound healing, longer than 1 month. We performed a microbiological study of wound contents and assessed the frequency of use of different antibiotics to combat infection. At the same time, pain intensity was assessed using a numerical pain rating scale. Patients were divided into two groups: uncomplicated infection and superinfection. Statistical analysis was performed using t-tests, Fisher's exact test, and multiple linear regression.ResultsSuperinfection was found in 50% of patients and was significantly associated with higher pain intensity (p < 0.01). Based on the results of the regression analysis, superinfection was found to be an independent predictor of pain severity (β = 1.31; p = 0.001). The use of aminoglycosides and carbapenems showed a trend towards increased pain scores, although statistical significance was not achieved.ConclusionsWound superinfection is a distinct predictor of the development of chronic pain after traumatic injury. Early microbiological monitoring and cautious use of neurotoxic antibiotics may reduce long-term pain in affected patients. For a deeper understanding of the processes and factors that contribute to and potentiate the development of pain syndrome, further studies are needed on microbial-neuroimmune interactions, taking into account the duration of antibiotic use and their combinations.